(untitled) (Bangladesh Journal of Psychiatry, 2020)
Tourette’s disorder is a childhood onset neuropsychiatric disorder characterized by multiple motor and vocal tics for at least one year in duration. Occasionally this disorder may be associated with obsessive compulsive disorder. This case was presented here to demonstrate the co-occurrence of these two disorders as well as the effectiveness of pharmacological treatment for the improvement of the condition. The case report described the history of a 21 years old male patient with 7 years history of Tourette’s disorder and obsessive compulsive disorder. He was seriously disabled by his symptoms that necessitated thorough evaluation to exclude causes, differential diagnoses and or any other co morbidities. Treatment with fluoxetine 60 mg daily and quitiapine 100 mg daily in divided dose improved his symptoms and he was able to return his functional life, that he had been mislaid because of his illness. Bang J Psychiatry June 2017; 31(1): 24-26